(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Rheumatoid arthritis is a chronic, progressive inflammatory disease that causes pain, swelling, and disability, severely affecting up to 50% of patients’ quality of life. Objective: To find out the association between disease severity of Rheumatoid Arthritis and QOL among patients. Methods: The present study was conducted at Sir Ganga Ram Hospital, Lahore from January to March 2024 A total of 120 patients with RA were enrolled by convenient sampling technique in this descriptive cross-sectional study. All patients with age >18 years, all genders and no mental illness or disturbance of consciousness were included. Pregnant females, and patients with severe co morbidities such as cancer or end stage organ failure were excluded. Demographic details, presenting symptom, disease severity assessed by Disease activity score-28 (DASS-28) and Quality of Life were recorded using a pre-designed proforma. The collected data was analyzed by using SPSS V24.0 software. The association between QOL and pain with disease severity was compared by using chi-square test. P-value ≤ 0.05 was considered as significant. Results: The association between quality of life (QOL), pain levels, and disease activity was significant(P-value<0.05); 90.0% of participants with high disease activity reported poor QOL, and severe pain was more prevalent (64.6%) in this group compared to those with low disease activity (33.3%). Conclusion: The study revealed a significant association between disease severity, pain, and overall patient quality of life. These findings indicate that higher disease activity correlates with increased pain severity and a diminished quality of life among participants.